Best Answer

x2+11x+11 = 7x+9

x2+11x-7x+11-9 = 0

x2+4x+2 = 0

The above quadratic equation can be solved by using the quadratic equation formula and it will have two solutions.

Q: What is the quadratic of this equation x2 plus 11x plus 11 equals 7x plus 9?

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

The discriminant is 0.

your equation is this... 2x3 + 11x = 6x 2x3 + 5x = 0 x(2x2 + 5) = 0 x = 0 and (5/2)i and -(5/2)i

5x + 32 = 11x - 105x - 11x = -10 - 32-6x = -42x = 7

8x - 9 = 11x + 12 8x = 11x + 21 -3x = 21 x = -7

x + 20 + 10x = 20 + 9x 11x + 20 = 20 + 9x Subtract 20 from both sides: 11x = 9x Subtract 9x from both sides: 2x = 0 Divide both sides by 2: x = 0

Related questions

The discriminant is 0.

X2+11x+11 = 7x+9 X2+11x-7x+11-9 = 0 x2+4x+2 = 0 Solve as a quadratic equation by using the quadratic equation formula or by completing the square: x = -2 + or - the square root of 2

The given expression is a quadratic equation. To find its solutions, we can either factor the equation or use the quadratic formula. However, without an equation to solve or any context, it is not possible to provide a numeric answer.

It is B, 0.

If 6x + 10 = 11x , then x=2.

9x2+11x-14 = (9x-7)(x+2) when factored with the help of the quadratic equation formula.

The equation -30 times -10 plus 11X equals -29. This is a math problem.

x=4 x=0

By using the quadratic equation formula: (4x+1)(x-3) = 0

That's an equation where x = 5

x2+11x+121 = x+96 x2+11x-x+121-96 = 0 x2+10x+25 = 0 Discriminant = b2-4ac = 102-4*1*25 = 0 The discriminant is equal to 0 so the quadratic equation will have two equal roots. (x+5)(x+5) = 0 Therefore: x = -5 and also x = -5 the answer is 0

It is a linear equation in a single variable, x.